2006
DOI: 10.1161/01.hyp.0000198425.21604.aa
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-Activated Protein Kinase Enhances Angiotensin II–Induced Proliferation in Cardiac Fibroblasts

Abstract: Abstract-AMP-activated kinase (AMPK) is a highly conserved heterotrimeric kinase that functions as a metabolic regulator of cellular enzymes involved in carbohydrate and fat metabolism, which regulate ATP conservation and synthesis. Here, we investigated whether AMPK signaling has a role in the regulation of angiotensin II (Ang II)-induced proliferation in rat cardiac fibroblasts. Aminoimidazole-4-carboxamide-1-␤-ribofuranoside (AICAR) activated AMPK in rat cardiac fibroblasts and increased Ang II-induced extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…On the other hand, AMPK phosphorylation occurred upon treatment with PDGF, a potent mitogen (Figs 2 and 3), which suggests that AMPK activation may not be strictly associated with growth inhibition. Although these data do not agree with the concept that AMPK has anti-proliferative activity (Motoshima et al 2006), two recent reports have shown that AMPK promotes the proliferation of osteoblastic cells and fibroblasts (Hattori et al 2006, Kanazawa et al 2008. In agreement with these findings, inhibition of AMPK blocked SMC proliferation in response to both PDGF and adiponectin, which thus implies that AMPK likely has a role in SMC proliferation.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, AMPK phosphorylation occurred upon treatment with PDGF, a potent mitogen (Figs 2 and 3), which suggests that AMPK activation may not be strictly associated with growth inhibition. Although these data do not agree with the concept that AMPK has anti-proliferative activity (Motoshima et al 2006), two recent reports have shown that AMPK promotes the proliferation of osteoblastic cells and fibroblasts (Hattori et al 2006, Kanazawa et al 2008. In agreement with these findings, inhibition of AMPK blocked SMC proliferation in response to both PDGF and adiponectin, which thus implies that AMPK likely has a role in SMC proliferation.…”
Section: Discussioncontrasting
confidence: 57%
“…AMPK is a serine/threonine protein kinase, which serves as an energy sensor in all eukaryotic cell types. Activation of AMPK strongly suppresses cell proliferation in nonmalignant cells as well as in tumor cells (15,16). The action of AMPK appears to be mediated through multiple mechanisms, including regulation of the cell cycle and inhibition of protein synthesis (16).…”
mentioning
confidence: 99%
“…The effects of H 2 O 2 on DNA and collagen synthesis in cardiac fibroblasts were evaluated by the incorporation of [ 3 H]-thymidine and [ 3 H]-proline into cells, respectively, as described previously (Hattori et al, 2006). To examine DNA synthesis, 0.5 mCi of [ 3 H]-thymidine was added 12 h after treatment with H 2 O 2 , and the cells were incubated for 12 h. To examine collagen synthesis, 0.5 mCi of [ 3 H]-proline was added 12 h after treatment with H 2 O 2 , and the cells were incubated for 24 h. After labeling, the cells were rinsed twice with cold PBS and incubated with 10% trichloroacetic acid at 4 1C for 30 min.…”
Section: Analysis Of Dna and Collagen Synthesismentioning
confidence: 99%